Eutrophication investigation and assessment of the Daning River after water storage of the Three Gorges Reservoir - 钟成华 幸治国 赵文谦 王德蕊 邓春光 李永健 幸梅 (Acta geochimica, 2005)
The Daning River is a very important tributary in the Three Gorges Reservoir area. It is also a famous scenic spot. Anomalies appeared after water storage of the reservoir in June, 2003. In September, 2003, eutrophication monitoring in the 135-m backwater reach of the Daning River was conducted and the data were simply analyzed. The assessment result is that water body in the segment from Shuauglong to Longmen was mesotrophic or eutrophic. At the same time, the causes of its nutritional change were discussed, and counter-measures have been proposed.